Plastic Cutlery Alternative: Case Study with Biodegradable Spoons - Dordevic, Dani; Necasova, Lucie; Antonic, Bojan; Jancikova, Simona; Tremlová, Bohuslava (Foods (Basel, Switzerland), 2021)
Plastics are mixtures of organic polymers that play a major role in environmental contamination worldwide. One way to reduce the waste arising from the use of plastics, especially disposable ones, can be to produce environmentally friendly cutlery. The aim of the work was the production of biodegradable spoons and evaluation of their texture, antioxidant activities and total polyphenols content. The spoons were made from a combination of the following ingredients: water, grape, proso millet, wheat, xanthan and palm oil in different concentrations. The samples were baked at 180 or 240 °C, some spoons were dried in a fruit dehydrator. According to the results of the analysis, a spoon prepared from a mixture of all three flours and with the addition of xanthan appears to be the most suitable replacement for plastic cutlery. This spoon showed high strength and antioxidant activity. It was confirmed that the use of grape flour has a beneficial effect on the nutritional profile of the experimentally produced biodegradable spoons.
Keywords: plastics; biodegradable spoons; polyphenols; antioxidant activity; texture